Strategi Optimalisasi Beban Administratif Guru SD Muhammadiyah 3 Pandaan melalui Penggunaan Aplikasi Digital "SIDIKMU" - Milatun Nadifa; Achmad Supriyanto; Rochmawati Rochmawati (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to evaluate the use of digital applications in reducing teachers' administrative burden at SD Muhammadiyah 3 Pandaan. In the digital age, excessive administrative workload can disrupt the quality of learning. The integration of digital technology in school management is the main solution, using a qualitative approach with a location at SD Muhammadiyah 3 Pandaan. Informants in this study included the principal, the vice principal for public relations, and four class teachers. Data collection is done through interviews and documentation. Data analysis uses a thematic approach with steps in the form of a transcription of interviews, identification of key themes from the collected data, preparation of findings, and validation of data with participants to ensure accuracy and depth of understanding. The results show significant benefits of such applications, such as increased efficiency and focus on teaching. The findings of this study underscore the importance of optimizing the use of digital applications to improve the quality of education. The PDCA strategy is used to ensure successful implementation. More research is needed to develop more effective digital applications across a variety of educational contexts.